Transdifferentiation of rat keratinocyte progenitors to corneal epithelial cells by limbal niche via the STAT3/PI3K/AKT signaling pathway - Bei Wang; Jiang-Lan Zhao; Gong-Yue Wang; Wan-Ying Cai; Yu-Ting Xiao; Jia-Song Wang; Chao Wang; Yu-Zhi Li; Xi Peng; Tian-Yu Yao; Ming-Chang Zhang; Hua-Tao Xie (Stem Cell Research & Therapy)
Abstract Purpose To develop a method for enriching keratinocyte progenitor cells (KPCs) and establish a limbal niche (LN)-mediated transdifferentiation protocol of KPCs into corneal epithelial cells. Methods Limbal niche cells (LNCs) were isolated from limbal tissues through enzymatic digestion and characterized. Conditioned medium from LNCs cultures was collected. KPCs were enriched by rapid adhesion of Matrigel and subsequently cultured in either an LNCs-conditioned medium supplemented with KSFM (LN-KS) or SHEM (LN-SH) for 14 days. Corneal-specific marker expression was assessed to evaluate transdifferentiation efficiency. Key transcription factors and signaling pathways involved in the transdifferentiation process were identified through single-cell and RNA sequencing, and were validated by western blot and quantitative real-time PCR. Results Both LN-KS and LN-SH protocols successfully induced corneal epithelial cell transdifferentiation from KPCs, with LN-KS demonstrating higher efficiency in generating CK12 + and p63 + cells (p < 0.001). RNA sequencing analysis and western blot have revealed significant activation of STAT3 and PI3K/AKT signaling pathways. Inhibition of STAT3 blocked the activation of PI3K/AKT signaling pathway and impaired corneal epithelial cell transdifferentiation. Conclusions This study demonstrates the ability of LN to promote KPCs transdifferentiation into corneal epithelial cells in vitro, and this process is partially mediated by the STAT3/PI3K/AKT signaling pathway. Graphical abstract